Delineation of the Prostate Bed: The “Invisible Target” Is Still an Issue? - Latorzeff, Igor; Sargos, Paul; Loos, Geneviève; Supiot, Stéphane; Guerif, Stéphane; Carrie, Christian (Frontiers in Oncology, 2017)
For pathological high risk prostate cancer, adjuvant irradiation has shown a survival benefit. Phase III studies have highlighted that half men would face biochemical relapse and would be candidate for radiotherapy at adjuvant or salvage times. Despite at least 4 published international contouring guidelines from different collaborative groups, discrepancies remain for volumes, delineation and margins to be considered in order to optimize radiotherapy planning. This article from GETUG members “Groupe d'Etude des Tumeurs UroGénitales (GETUG)” will focus on controversies to help clinicians to create best volume delineation for adjuvant or salvage post prostatectomy radiotherapy